Histone Deacetylase Inhibitors Are Protective in Acute but Not in Chronic Models of Ototoxicity - Yang, Chao-Hui; Liu, Zhiqi; Dong, Deanna; Schacht, Jochen; Arya, Dev; Sha, Su-Hua (Frontiers in Cellular Neuroscience, 2017)
Previous studies have reported that modification of histones alters aminoglycoside-induced hair cell death and hearing loss. In this study, we investigated three FDA-approved histone deacetylase (HDAC) inhibitors (vorinostat/SAHA, belinostat, and panobinostat) as protectants against aminoglycoside-induced ototoxicity in murine cochlear explants and in vivo in both guinea pigs and CBA/J mice. Individually, all three HDAC inhibitors reduced gentamicin-induced hair cell loss in a dose-dependent fashion in explants. In vivo, however, treatment with SAHA attenuated neither gentamicin-induced hearing loss and hair cell loss in guinea pigs nor kanamycin-induced hearing loss and hair cell loss in mice under chronic models of ototoxicity. These findings suggest that treatment with the HDAC inhibitor SAHA attenuates aminoglycoside-induced ototoxicity in an acute model, but not in chronic models, cautioning that one cannot rely solely on in-vitro experiments to test the efficacy of otoprotectant compounds.